2021
DOI: 10.3389/fmicb.2021.710346
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Urban Beach Quality on a Summer Day: Determination of the Origin of Fecal Indicator Bacteria and Antimicrobial Resistance at Prophète Beach, Marseille (France)

Abstract: A highly frequented beach in Marseille, France, was monitored on an hourly basis during a summer day in July 2018, to determine possible water and sand fecal pollution, in parallel with influx of beach users from 8 a.m. to 8 p.m. Fecal indicator bacteria were enumerated, together with four host-associated fecal molecular markers selected to discriminate human, dog, horse, or gull/seagull origins of the contamination. The antimicrobial resistance of bacteria in water and sand was evaluated by quantifying (i) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Limitations of the study include the period during which the analyses were performed (November–June), since the microbial contamination of human origin is expected to increase significantly during the summer season, due to the increased presence of people on the beaches [ 43 ]. Thus, the study should be extended to summer period to get generalizable results.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study include the period during which the analyses were performed (November–June), since the microbial contamination of human origin is expected to increase significantly during the summer season, due to the increased presence of people on the beaches [ 43 ]. Thus, the study should be extended to summer period to get generalizable results.…”
Section: Discussionmentioning
confidence: 99%
“…HF183 has been consistently detected in beach waters along California coast (Cao et al, 2017; McQuaig et al, 2012; Russell et al, 2013; Sercu et al, 2009), and public health risks have been estimated based on quantitative microbial risk assessment (QMRA) of HF183 detection levels (Boehm et al, 2015; Brown et al, 2017). Correlations between swimmers and the presence of low levels of HF183 have been reported, suggesting bather shedding as a source of HF183 to recreational waters (Li, Van De Werfhorst, Steets, Ervin, Murray, Blackwell, et al, 2021; Li, van De Werfhorst, Steets, Ervin, Murray, Devarajan, & Holden, 2021; Toubiana et al, 2021). The results of this study may inform such correlations by suggesting that B. dorei in skin or urine microbiomes of bathers might contribute to the observed low levels of HF183 in environmental waters.…”
Section: Discussionmentioning
confidence: 99%
“…HF183 was also consistently observed in beach waters along the California coast in many previous studies associated with sampled drainage, creek and river waters (Cao et al, 2017; McQuaig et al, 2012; Russell et al, 2013; Sercu et al, 2009). In recent studies of several beaches, swimmers were found to be sources of chronic, low concentration, HF183 markers in beach surf zone waters (Li, Van De Werfhorst, Steets, Ervin, Murray, Blackwell, et al, 2021; Li, van De Werfhorst, Steets, Ervin, Murray, Devarajan, & Holden, 2021; Toubiana et al, 2021). These results raised the question: could aquatic HF183 detections originate from other than human faecal releases or faecal shedding into the environment?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of studies have focused on recreational beach waters, which are greatly associated with human activities and public health. Humans/sewage inputs have been frequently identified as the major pollution sources on public urban beaches [92], urban runoff-impacted beaches [93], marine beaches [94], coastal beaches [95], and surfing beaches [96], often using HF183 and HumM2 MST markers. Bathers and beach users/visitors were considered to contribute directly and significantly to the resulting fecal pollution, which is exacerbated by stormwater discharge.…”
Section: Sea/salt Watersmentioning
confidence: 99%